Implementation of Information Technology (IT) in Education Marketing - Yusuf, M.; Asmoni; Jamilah; Yuliati; Rahman, Taufik; Dwiyanti, Linda; Sari, Rini Ratna Nafita; Kusrini, Nurul Azizah Ria; Hariyani, Tuwis (International Journal of Psychosocial Rehabilitation, 2020)
Today, the development of technology and information has been advancing rapidly. Its existence has also entered into various aspects of life, the business world, government, social organizations, and all associations, many of which have used sophistication to help facilitate their activities, not to forget the world of education. However, if seen, there are only a few educational institutions that are aware and willing to utilize the power of technology and information to implement it in all operational, educational activities, even if it is carried out, there will inevitably be an extraordinary jump to the progress of education which will, in turn, take part also supports the progress of our beloved Indonesian nation. What is the power of information technology in education marketing, what is the purpose of the application of information technology in education marketing, and what are the effects of using information technology for school managers? The research used in this paper is the qualitative research method, in which the author uses several references to compile and support some data and views by the research formulation. From this study, it can be concluded that the use of IT in marketing madrasah education will run effectively and efficiently, especially in the era of all-sophisticated as now, the target and the intended destination are also increasingly broad and on target. The management of educational institutions, especially operators or marketing officers, is not rigid in carrying out their duties. Besides, budget efficiency can be done very well if, in marketing education, it utilizes technological and information advancements.